Modeling Of Double- Fillet Tee joint in solidwork simulation (University of Thi-Qar Journal for Engineering Sciences, 2017)
The research aims to study and simulation weld joint type Double –Fillet Tee Joint ,It was studied stress concentration along the weld area and calculate the required weld size under effect variable loads (1,2,4)kN by using Finite Element Method through a program Solidwork Simulation 2013.It has been identified weld size (4mm) as the value of fixed for all loads, this value is proposed from welding of scientists as the default value ranging (4-10)mm and used a feature (Edge Weld Check Plot) in solidwork program .It has compared the theoretical results with the analytical results ,the ratio of error was less than (2%) .It has simulation by draw 3D solid model and convert it to shell model with loads and fixture .The results showed that the maximum value of the stress is (10)N / mm2 under load (4)kN and less thickness necessary for the welding connection is 0.132 mm under load (1)kN The more load on joint weld will increases weld size required without afailure.The research supplies recommendations for precision of solidwork simulation to be used as design device calculate the joints.